Media Policy and Globalization - Paula Chakravartty , Katharine Sarikakis (Edinburgh University Press, 2006)
From the conception to its publication, this book has been a rich, enjoyable and, at times, frustrating transnational journey where we both learned a great deal, not only about our subject matter but also about ourselves. The road was longer than we anticipated, but only because life is unstoppable and all present: the book apart from the standard daily routines of leading full academic lives, the winter flues included, witnessed a research leave and multiple stays abroad, four house moves, the birth of a baby girl (Aisha), two job moves and a wedding, and throughout these life experiences our families and friends made the process more enjoyable. Our journey to this ‘Ithaca’ has made us richer in knowledge and friendship, collegiality and confidence. This book explores the conditions and ideas behind global communications policies; our writing travels back and forth, across continents and socioeconomic realities to identify and analyze common policy concerns, conflicting interests, and the place and voice of publics. Throughout the writing process, we relied heavily on electronic communications to update information, track down electronic archives and conduct basic literature searches. We conceived and discussed the ideas in this book first online and then by telephone and continued developing the book in the same way, with only one brief off-line meeting. We have used six different computers between us (two of which crashed) and have been dependent on Internet access with speedy connections (broadband). These tools were available to us as researchers based in academic institutions, in our homes and hotels and Internet cafes located in the connected parts of the world where we wrote this book – Amherst, Athens, Coventry, Kolkata, London, Montreal, Pittsburgh and Salvador – enabling us to communicate with colleagues across the world instantly